2012
DOI: 10.3844/ajidsp.2012.65.69
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Sensitivity Pattern of Blood Isolates of <i>Acinetobacter</i> Species in a Tertiary Care Hospital: A Retrospective Analysis

Abstract: Problem statement: Multi-drug resistant Acinetobacter bacterium is one of the major causes of sepsis in ICUs in tertiary care hospitals in India. In this report we describe the antibiotic sensitivity patterns of Acinetobacter species isolated from blood over a one year period at a tertiary care hospital. Approach: We retrospectively analyzed the sensitivity pattern of Acinetobacter species isolated from blood during the period 1/6/2010 to 31/5/2011. Isolation and identification were performed using the best al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 21 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…All isolates were susceptible to colistin. O t h e r s t u d i e s b y ( Shareek et al 2012;Dash et al 2013;Saha et al 2018) also reported colistin as the most sensitive drug.…”
Section: Discussionmentioning
confidence: 95%
“…All isolates were susceptible to colistin. O t h e r s t u d i e s b y ( Shareek et al 2012;Dash et al 2013;Saha et al 2018) also reported colistin as the most sensitive drug.…”
Section: Discussionmentioning
confidence: 95%
“…are A. baumannii, followed by A. lwoffii. A. junii accounts for less than 1% of isolates [8]. Although these infections are mainly attributed to Acinetobacter baumannii as a clinically and epidemiologically most important pathogen of the genus.…”
Section: Discussionmentioning
confidence: 99%